2019
DOI: 10.1515/biol-2018-0058
|View full text |Cite
|
Sign up to set email alerts
|

Emodin promotes apoptosis of human endometrial cancer through regulating the MAPK and PI3K/ AKT pathways

Abstract: Emodin, a major component of rhubarb, has anti-tumor effects in a variety of cancers, influencing multiple steps of tumor development through modulating several signaling pathways. The aim of this study is to examine the effect of emodin on cell apoptosis and explore the underlying mechanisms in human endometrial cancer cells. Here we report that emodin can inhibit KLE cell proliferation and induce apoptosis in a time- and dose-dependent manner. Western blot assay found that emodin was involved in MAPK and PI3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…AKT signaling promotes cell survival by mediating the effects of cellular growth factors, and blocks apoptosis by inactivating pro-apoptotic proteins [53]. Inhibition of AKT phosphorylation has shown promising results in restraining endometrial cell proliferation [54,55]. Based on its role in cancer progression, various inhibitors of PI3K/AKT/mTOR are currently being evaluated in clinical trials for treating patients with metastatic, recurrent, and persistent endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…AKT signaling promotes cell survival by mediating the effects of cellular growth factors, and blocks apoptosis by inactivating pro-apoptotic proteins [53]. Inhibition of AKT phosphorylation has shown promising results in restraining endometrial cell proliferation [54,55]. Based on its role in cancer progression, various inhibitors of PI3K/AKT/mTOR are currently being evaluated in clinical trials for treating patients with metastatic, recurrent, and persistent endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the decreased level of expression, the high level of deep deletion within the gene and differences in methylation may in uence post-transcriptional regulation and phosphorylation of the gene, in uencing its ability to self-activate. For example, therapeutics such as emodin which target phosphorylation are shown to maintain basal levels of genes involved in the p38MAPK pathway while inducting ROS activated apoptosis of cancer cells [47,74] Activation of p38β via the transcription factor Pokemon/Zbtb7 is associated with tumorigenesis and cell invasion in HepG2 cells [30]. Downstream signalling of p38β also leads to an increase in expression of the oncogene, Lipocalin2 (LCN2), and an increase in tumour cell migration [18,30].…”
Section: Methodsmentioning
confidence: 99%
“…mechanism for future research [47]. Studies have shown that oestradiol is a potential activator of the MAPK pathway through estrogen (ER) and Insulin receptor (InsR) interaction.…”
Section: Regulation Of Cell Proliferation -Differentiation By Mapk VImentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of emodin on cell proliferation was studied and confirmed for many cancer cell lines, including breast [40], skin [41], pancreas [42], colon [43,44], ovarian [45], prostate [46], esophageal [47], bladder [48], and endometrial [49]. For example, the IC50 values for MCF-7 (breast) and HepG2 (liver) cancer cells were 52.72 μM and 43.87 μM, respectively [50].…”
Section: Proliferationmentioning
confidence: 98%